Exploring Augmented Reality-Based Learning Media Implementation in Solar System Materials - Muhammad Andika Putra; Madlazim Madlazim; Eko Hariyono (IJORER : International Journal of Recent Educational Research, 2024)
Objective: This research aims to analyze the impact of using augmented reality (AR) based learning media on understanding Solar System material. The focus is on evaluating the effectiveness of AR in improving the learning process, particularly on Solar System materials. Methods: The research method used is a literature review by searching for related journals indexed by Scopus within the last five years, from 2018 to 2023. The selected literature was then analyzed to gain an in-depth understanding of the implementation of AR in Solar System learning. Results: Analysis of the literature shows that using AR technology as a learning medium positively impacts understanding of Solar System concepts. There is an increase in student engagement and learning effectiveness through AR. Novelty: This study reveals that using AR-based learning media on solar system material can improve understanding of Solar System concepts. This finding invites researchers, teachers, and the government to develop and consider the implementation of AR in the context of astronomy learning.